DESAIN DINDING INTERIOR PANGGUNG BALERUNG SRINERTYA WADITRA DI PELIATAN - A.M., A.A. GD. Tugus Hadi Iswara (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The rapid development of tourism in Bali will mark the existence of a characteristic in a design that can Show the identity of each region,which can attract tourists to visit Bali, especially at Peliatan village. It play role in development of environment in the area of tourism and entertainment by not leaving the meaning of the elements of tradition.Ancient times in Kori Agung Agung Puri Peliatan has function as the entrance of the castle and also used as a place of dance and gambelan performances watched by the kings and his people. The preservation and cultural aesthetic security is maintained even though the function has been changed from the entrance of Puri became the design of the wall of the stage. Balerung is venue of Peliatan art performances in Peliatan village. On the basis of these activities Balerung Srinertya Waditra using Kori Agung Puri Agung Peliatan as a wall design on the stage that still preserve elements of culture.